2001
DOI: 10.1124/mol.60.5.955
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of β-Adrenergic Receptor Subtypes in Blood Vessels of Knockout Mice Lacking β1- or β2-Adrenergic Receptors

Abstract: beta-Adrenergic receptors (beta-AR) are essential regulators of cardiovascular homeostasis. In addition to their prominent function in the heart, beta-AR are located on vascular smooth muscle cells, where they mediate vasodilating effects of endogenous catecholamines. In this study, we have investigated in an isometric myograph different types of blood vessels from mice lacking beta(1)- and/or beta(2)-adrenergic receptor subtypes (beta(1)-KO, beta(2)-KO, beta(1)beta(2)-KO). In wild-type mice, isoproterenol ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 28 publications
5
66
1
4
Order By: Relevance
“…The action of ␤-adrenergic receptors involves stimulation of adenylyl cyclase via interaction of the agonist-receptor complex with G s and subsequent intracellular cAMP concentration increase (25). In addition, relaxation could be elicited by direct activation of adenylyl cyclase (22). This signal transduction pathway has also been described for CFTRdependent secretion in epithelia (14).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The action of ␤-adrenergic receptors involves stimulation of adenylyl cyclase via interaction of the agonist-receptor complex with G s and subsequent intracellular cAMP concentration increase (25). In addition, relaxation could be elicited by direct activation of adenylyl cyclase (22). This signal transduction pathway has also been described for CFTRdependent secretion in epithelia (14).…”
Section: Discussionmentioning
confidence: 93%
“…The cAMP pathway is an important regulator of the vascular tone. In this regard, ␤-adrenergic receptors are located on vascular smooth muscle cells and mediate vasodilating effects of endogenous catecholamines (22,25). The action of ␤-adrenergic receptors involves stimulation of adenylyl cyclase via interaction of the agonist-receptor complex with G s and subsequent intracellular cAMP concentration increase (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies found that both AR-b 1 and AR-b 2 were downregulated in SHR. [28][29][30][31] Chruscinski et al 32,33 reported that AR-b 1 had a dominant role in mediating vasodilation in mice. Hirota et al 34 found AR-b 2 stimulation improved inotropic and lusitropic function in the failing heart and Communal et al 35 reported that AR-b 2 inhibited cardiocyte apoptosis through a Gi-coupled pathway in rats.…”
Section: Discussionmentioning
confidence: 99%